Cultural diversity and subjective well-being - Simonetta Longhi (IZA Journal of Migration, 2014)
This paper analyses the impact that diversity has on life satisfaction of people living in England. In England, and in many other countries, local communities are becoming more diverse in terms of country of birth, ethnicity and religion of residents, with unclear consequences on the well-being of people living in these communities. The results suggest that white British people living in diverse areas have on average lower levels of life satisfaction than those living in areas where diversity is low, while there is no correlation on average between diversity and life satisfaction for non-white British people and foreign born.
Keywords: J31; J61; R23; 330; Diversity; Individual subjective well-being; Local Authority Districts